The Impact of ESG Pillars on Banking Financial Performance in ASEAN-5 Countries - Muhammad Hilman Rizki; I Nyoman Nugraha Ardana Putra (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose: This research analyzes the effect of ESG pillars on the financial performance (ROA) of banking companies in ASEAN-5 countries.Method: The study utilizes ESG data sourced from Thomson Reuters Eikon Refinitiv. The research population comprises 91 banks from ASEAN-5 countries, with a sample size of 25 banks selected for analysis. The observation period spans 2019 to 2023. Panel data regression analysis was conducted using Eviews 12 software to evaluate the data.Result: The findings reveal that, during the 2019–2023 period, the environmental and social pillars of ESG do not significantly impact the ROA of banking companies in ASEAN-5. However, the governance pillar demonstrates a significant positive relationship with ROA, indicating that corporate governance practices play a key role in enhancing the financial performance of banks in the region.Practical Implications for Economic Growth and Development: This study contributes to economic growth and development by emphasizing the critical role of corporate governance in improving the financial performance of banking firms in ASEAN-5. The findings suggest that robust governance practices can boost operational efficiency, attract investment, and enhance financial stability—factors essential for sustainable economic growth. Policymakers can leverage these insights to design targeted incentives that encourage banks to strengthen their governance frameworks, fostering a more resilient banking sector in Southeast Asia.